The Effectiveness of Wordwall Games in Developing the Vocabulary Mastery of Seventh Grade Students at SMP Negeri 19 Palu - Nurwirda Nurwirda; Jamiluddin Jamiluddin; Grace Novenasari Manurung; Nur Sehang Thamrin (Journal of Education Research, 2026)
Vocabulary mastery is a fundamental aspect of English language learning that enables students to comprehend and use language effectively. However, seventh-grade students at SMP Negeri 19 Palu still experience difficulties in understanding word meanings and using vocabulary appropriately in sentences. This study aimed to examine the effectiveness of the Wordwall game on students’ vocabulary mastery, particularly in terms of word meaning and word usage. The study employed a quasi-experimental design with a pretest-posttest control group design involving 60 students divided into an experimental group and a control group. Data were collected through vocabulary tests administered before and after the treatment and were analyzed using an independent sample t-test. The findings revealed that the experimental group achieved a mean post-test score of 82.47, while the control group obtained a mean score of 71.15. Statistical analysis showed a significance value of p = 0.001 (p < 0.05), indicating a significant difference between the two groups. These findings demonstrate that the Wordwall game is effective in improving students’ vocabulary mastery compared to conventional teaching methods. Pedagogically, the study suggests that Wordwall can be utilized as an interactive learning medium to enhance students’ motivation and vocabulary achievement in English language learning.